O Empregado “hipersuficiente” e a arbitragem: as incompatibilidades jurídicas do art. 507-A, da CLT à luz da Lei Brasileira de Arbitragem (Lei n. 9.307/96) - CONCEIÇÃO, João Paulo Pantoja (2022)
Among several controversial topics inserted by Law nº 13,467, also known as Labor Reform, highlights the possibility of free stipulation on contractual relations by interested parties, which inaugurates the notion of the “hypersufficient” employee (art. 444, sole paragraph, of the CLT), and allows the adoption of arbitration to resolve conflicts arising from employment contracts signed with these employees, pursuant to art. 507-A, of the CLT. In this way, the present essay will develop on the vicious nature of the eventual arbitration clause agreed during the term of the employment contract, considering that the proposition of arbitration procedures within the scope of individual labor law only hurts the parameters of arbitrability both objective and subjective provisions of the Brazilian Arbitration Law (Law 9,307 / 96), even going against the very structure of the Labor Court - which is of a protective nature - in view of the patent legal incompatibility between these two areas of law.